Research ability in Chemistry and the Tuning Latin America specific competences: a comparative study at University of Cuyo (Argentina) - Dias, Iris Valeria (2014)
Research ability can be thought of as a competence, which requires other abilities — both generic and specific — to be successfully developed. In this study, we determine the degree of importance that the 21 specific competences (SCs) established in the Tuning Latin America (Tuning-LA) Project, have in the acquisition of research ability in Chemistry, as a result of taking the degree program offered at the Facultad de Ciencias Exactas y Naturales, Universidad Nacional de Cuyo (FCENUNCUYO, Mendoza, Argentina). To this end, we adopted the SCs proposed as learning objectives in undergraduate studies in Chemistry, and consulted academics and students at FCEN-UNCUYO about (1) the importance of these competences in his/ her opinion for work in the profession; (2) the level of achievement of these competences, that they estimated was reached as a result of taking the FCEN-UNCUYO degree program in Chemistry; and, (3) the relevance of the Tuning-AL specific competences for the development of research ability in Chemistry. The results of the survey at FCEN-UNCUYO are compared with those obtained by consulting academics and students in the framework of the Tuning-LA Project. Detailed comparisons between the opinion of academics and students at FCEN– UNCUYO are also reported.